Elaboração e validação de conteúdo do instrumento para mensurar a intensificação do trabalho da enfermagem: estudo metodológico - Arboit, Eder Luis (2022)
Introduction: nowadays, workers from different sectors have been influenced in their work processes, which can be attributed to the capitalist/neoliberal models, with emphasis on aspects such as: precariousness of work, fragility in work relationships, multifunctionality and versatility requirement, as well as an increase in the pace of work. In the area of health and, in particular, in nursing, workers have also been impacted by these changes, which have resulted in the intensification of work. Objective: to elaborate and validate the content of the instrument to measure the intensification of nursing work. Method: methodological study carried out in five stages: I - Clearly determine what you want to measure; II – General a pool of items; III - Determine the measurement format; IV - Have the set of items reviewed by experts; V - Consider the inclusion of validation items. The instrument elaboration process is anchored in the systematic literature review (2019-2020) and in the exploratory-descriptive study, with a qualitative approach (2021), which allowed to elucidate the content that best represents the items and domains related to the investigated construct. Study participants were 18 nursing workers in the exploratory stage (item elaboration), 12 PhDs who composed the committee of judges/experts and 43 nursing workers in the pre-test stage. Data processing took place through content analysis and calculation of the Content Validity Index. Results: the integrative review study identified factors related to the intensification of nursing work in the hospital environment, which refer to institutional/labor, human and clinical aspects. The exploratory study showed that, from the perspective of nursing workers, the intensification of work is linked to the lack of materials and equipment, the patient's clinical condition, weaknesses in professional training and qualification, intensified pace and work demands; weaknesses in management and interprofessional collaboration. The results of the mentioned steps allowed the elaboration of 62 items which were submitted to the evaluation of the expert committee, in a single round. The CVI ranged from 0.58 to 1.00, excluding items with a value lower than 0.80. The CVI of the domains ranged from 0.94 to 0.97. In the pre-test with the target population, the CVI ranged from 0.90 to 1.00. After making the adjustments, the final instrument contains 60 items distributed in seven domains. The instrument in its complete formation had a CVI of 0.95. Conclusion: the instrument is considered valid by the committee of judges/experts and by the target population, contributing to clinical and scientific practice. It constitutes an innovative tool to be used to measure the intensification of work in the context of nursing in the hospital environment, being ready for the initial examination of the performance of the items, through factor analysis.